Kompetencje samorządu zawodowego lekarzy w zakresie odpowiedzialności zawodowej w Polsce - Skrzypczak, Jędrzej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The subject of this study is the analysis of one of the competences of the professional self-governing bodies of medical doctors, namely the exercising of professional liability. Both the analysis of historical provisions and modern regulations confirms that the compe- tence of exercising professional liability is one of the most significant rights and responsibilities of the professional self-governing body of doctors. It should be remembered that the binding law on the chambers of medical doctors stipulates that it is a professional self-government’s task to represent individuals who perform the profession of doctor and den- tist, and to exercise care that these professions are performed within the limits of public inter- est and for its protection. Therefore, it seems that exercising of professional liability is the fundamental priority in the realm of ensuring appropriate performance of the profession.
The competences of the professional self-governing bodies of doctors with respect to professional liability in Poland
Keywords: samorząd zawodowy lekarzy; odpowiedzialność zawodowa